Human Umbilical Cord Mesenchymal Stem Cells Suppress Systemic Lupus Erythematosus Lesions by Rebalancing CD4+/CD8+ Cell Population - Chan Li; Hongfang Ju; Qiongshu Li; Xin Zhou; Xiaoping Zeng; Yixin He; Guifang Zeng; Jia Liu; Chunfeng Wu; Tenglong Yan; Wei Li; Jiuwei Cui; et al. (Studies on Stem Cells Research and Therapy - Peertechz Publications, 2015)
Despite considerable advances in the treatment for systemic lupus erythematosus (SLE), there is still an unmet need to develop novel therapeutic approaches with improved efficacy and lower side effects. Here we explore human umbilical cord-derived mesenchymal stem cells (hUCMSCs) as a promising treatment for SLE induced by concanavalin A-activated spleno-lymphocyte in BALB/c mice. The isolated hUCMSCs,  carrying specific MSC cell surface markers (CD105, CD73 and CD90), exhibited the potential to  differentiate into osteogenic and adipogenic lineages. In mice with SLE, transplantation of hUCMSCs  improved disease symptoms by decreasing the levels of serum autoantibody (antidsDNA and anti- nuclear) and cytokines (TNF-α and IFN-γ). The cell therapy significantly alleviated renal lesions by  lowering serum urea nitrogen, creatine and uric acid, and increasing albumin. Using immunohistochemical staining, we found that that hUCMSCs decreased endocapillary hypercellularity, glomerular degeneration,  and complement C3 immune complex deposition in the kidney. Mechanically, the therapy with hUCMSCs  decreased CD4+/CD8+ cell ratio in animals. These data suggest that hUCMSCs may modulate   autoimmunity in SLE mice by rebalancing CD4+/CD8+ cell population. Transplantation of hUCMSCs may  be explored as a promising alternative approach in the treatmentof human lupus.